Philippines : 2007 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Authorities of the Executive Director for the Philippines. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Economic stability of the Philippines was discussed in this report. Private investment remained low by regional standards, but there are tentative signs of a revival. These developments and favorable global conditions led to a surge in foreign exchange inflows and the external value of the peso. Inflation remained low because of an appreciating peso and prudent monetary policy. The authorities are encouraged to strengthen the tax effort. Legislation is being considered to restore the tax base by rationalizing fiscal incentives and adjusting excise taxes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet